EFL oral skills behaviour when implementing blended learning in a content-subject teachers’ professional development course - Sánchez Narváez, Natalia; Chavarro Vargas, Sergio Alberto (Colombian Applied Linguistics Journal, 2017)
The increasing use of technology in educational settings (Murray, 2014; Zandi, Thang, & Krish, 2014) encourages teachers to refocus their professional development by centering their efforts on becoming proficient in the use of information and communication technologies (ICTs) in language lessons (Chen, Chen, & Tsai, 2009). As such, this qualitative action research project intended to describe content-subject teachers’ EFL oral behavior when blended learning was implemented in a professional development course and to determine the influence of blended learning in EFL oral skill behavior. The participants were seven content-subject teachers from a private school in Huila, Colombia. Data were gathered via in-depth interviews, class observations, video recording analysis, teachers’ reflection, students’ artifacts, and a survey. Data were collected during the implementation of an English blended course in which 12 lessons were divided into six face-to-face sessions and six online meetings. The findings suggest that EFL oral skill behavior is connected with use of vocabulary, use of body language, pronunciation and intonation patterns, production of chunks of language, monitoring oral production and, motivation and engagement. In addition, blended learning influenced participants’ oral production.